2022
DOI: 10.1002/anr3.12190
|View full text |Cite
|
Sign up to set email alerts
|

Erector spinae plane block with catheter infusion for analgesia in a patient undergoing transaxillary first rib resection

Abstract: Analgesia for first rib resection can be challenging with short-and long-term consequences for patients such as acute distress, difficulty participating in physiotherapy and chronic pain. We report utilising an erector spinae plane block with a continuous infusion catheter as analgesia for a transaxillary first rib removal in a patient with venous thoracic outlet syndrome (Paget-Schroetter syndrome). We could find no reports of erector spinae plane block in transaxillary rib resection, and a limited number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…10,11 Few reports studies have studied erector spinae catheter use in multimodal pain management, especially in the setting of TOS decompression. A case study by McCance et al 12 found continuous ESP block to be an effective mode of analgesia in combination with NSAIDs and opioids but did not include direct comparison to paravertebral blocks such as the surgically placed catheters in the present study. Guffey et al 13 performed a comparative study of single-injection erector spinae injections and continuous perineural infusion catheters, finding that the injections were not inferior to the infusion catheters.…”
Section: Discussionmentioning
confidence: 92%
“…10,11 Few reports studies have studied erector spinae catheter use in multimodal pain management, especially in the setting of TOS decompression. A case study by McCance et al 12 found continuous ESP block to be an effective mode of analgesia in combination with NSAIDs and opioids but did not include direct comparison to paravertebral blocks such as the surgically placed catheters in the present study. Guffey et al 13 performed a comparative study of single-injection erector spinae injections and continuous perineural infusion catheters, finding that the injections were not inferior to the infusion catheters.…”
Section: Discussionmentioning
confidence: 92%
“…One retrospective study discussed the use of the pectoral block II with the transaxillary technique, but its conclusions reported no decrease in pain scores or opioid usage [ 5 ]. Another case report highlighted the effective analgesic results of a continuous ESP block used in the transaxillary method [ 6 ].…”
Section: Discussionmentioning
confidence: 99%